2001
DOI: 10.1007/s003300101031
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum of abdominal sonographic findings in 103 pediatric patients with Gaucher disease

Abstract: The purpose of this study was to catalogue spleen and liver features by US in a cohort of 103 pediatric patients with Gaucher disease, and to document response to enzyme replacement therapy by serial US examination. There were 42 boys and 61 girls, 2 were splenectomized. Forty-eight patients received enzyme replacement therapy (ERT). At presentation all patients evinced organomegaly and 4.9% had focal (splenic or hepatic) lesions (hypo- and hyper-echoic or mixed). Fifteen patients began ERT before 11 years of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 6 publications
(7 reference statements)
2
20
0
Order By: Relevance
“…3) and splenic response to ERT, thus identifying FSL as an important determinant of responsiveness to ERT. In keeping with previous studies, we found these splenic lesions were associated with older age and extent of splenomegaly (Neudorfer et al 1997; Patlas et al 2002; Lee 1982; Hill et al 1986; Chippington et al 2008). A new finding in our study was that FSL were associated with a higher incidence of osteonecrosis.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…3) and splenic response to ERT, thus identifying FSL as an important determinant of responsiveness to ERT. In keeping with previous studies, we found these splenic lesions were associated with older age and extent of splenomegaly (Neudorfer et al 1997; Patlas et al 2002; Lee 1982; Hill et al 1986; Chippington et al 2008). A new finding in our study was that FSL were associated with a higher incidence of osteonecrosis.…”
Section: Discussionsupporting
confidence: 92%
“…The incidental finding of FSL in a patient not yet diagnosed with GD1 may lead to misdiagnosis of malignancy and inappropriate splenectomy (Neudorfer et al 1997). Previous studies using ultrasonography or MRI estimated the prevalence of FSL to be 4% (pediatric) (Patlas et al 2002) to 33% (adult) (Lee 1982) of GD1 patients. Frequency of FSL increases with age: for example, 12/23 (52%) patients aged >18 years had splenic lesions compared to only 2/13 (8.9%) patients <18 years (Hill et al 1992).…”
Section: Introductionmentioning
confidence: 99%
“…Ultrasonography 54 CT scan or ideally MRI scan of the abdomen are used to determine liver and spleen volumes ( Figure 6). Focal accumulations of Gaucher cells "Gaucheromas" may be found in the liver or spleen.…”
Section: Imaging Organomegalymentioning
confidence: 99%
“…At minimum, monitoring disease expression and effects of ERT includes serial evaluation of hematological parameters and reduction in hepatosplenomegaly. Although ultrasonography may be recommended for repeat assessments as the least invasive and as having no risk of radiation, 33 especially in children, 34 it is the least used because of issues of reliability and reproducibility and the importance of observer experience. Computed tomography (CT) was universally employed in the past, 35 and today, magnetic resonance imaging (MRI), 36 especially because of justifiable concerns about radiation with periodic assessments is preferred.…”
Section: Enzyme Replacement Therapy (Ert): the Early Yearsmentioning
confidence: 99%